Ecoenzymatic stoichiometry reveals stronger microbial carbon and nitrogen limitation in biochar amendment soils: A meta-analysis - Chen, Zhe; Jin, Penghui; Wang, Hui; Hu, Tianlong; Lin, Xingwu; Xie, Zubin (The Science of the total environment, 2022)
Soil extracellular enzyme activities of microbes to acquire carbon (C), nitrogen (N) and phosphorus (P) exert great roles on soil C sequestration and N, P availability. However, a lack of biochar-induced changes of C, N and P acquisition enzyme activities hinders us from understanding if biochar application will lead to microbial C, N and P limitation based on ecoenzymatic stoichiometry. In this study, through ecoenzymatic stoichiometry, a meta-analysis was conducted to evaluate responses of microbial metabolic limitation to biochar amendment by collecting data of ecoenzymatic activities (EEAs) of the C, N and P acquisition from peer-reviewed papers. The results showed that biochar application increased activities of C, N acquisition enzymes significantly by 9.3 % and 15.1 % on average, respectively. But the influence on P acquisition enzymes activities (Acid, neutral or alkaline phosphatase, abbreviated wholly as PHOS) was not significant. Biochar increased ratio of C acquisition enzymes activities (EC) over P enzymes activities (EP) and ratio of N enzymes activities (EN) over EP, but decreased EC:EN, indicating an increased N limitation or a shift from P limitation to N limitation in microbial metabolism. Enzyme vector analysis showed that soil microbial metabolism was limited by C relative to nutrients (N and P) under biochar amendment according to the overall increased vector length (~1.5 %). Wood biochar caused the strongest microbial C limitation, followed by crop residue biochar as indicated by increased enzyme vector length of 3.6 % and 1.2 % on average, respectively. The stronger microbial C limitation was also found when initial soil total organic carbon (SOC) was <20 g·kg−1. Our results illustrated that available nitrogen and organic carbon should be provided to meet microbial stoichiometric requirements to improve plant productivity, especially in low fertile soils under biochar amendment. [Display omitted] •Biochar addition overall decreased EC:EN by 7.1 %, but increased EC:EP and EN:EP by 14.2 % and 22.6 %, respectively.•Biochar addition increased the enzyme vector length but decreased vector angle.•Soil microbial C and N limitation was intensified, but P limitation decreased with biochar addition.